Between Cultural Preservation and Tourism Industry: Dialectic Relations in Cultural Heritage Tourism Management in Tanah Lot and Borobudur Indonesia - Surya Diarta, I Ketut (E-Journal of Tourism; Volume 4 Number 2 (September 2017), 2017)
Cultural heritage tourism has a great role in supporting economic growth in Indoneisa. This can only be achieved if cultural heritage tourism is well managed. Well and integrated management refers to the balance of preservation of cultural heritage and tourism industry since both are two entities that have a contradictory management regime approach. This paper discusses the destination management model of two culural heritages: Borobudur Temple in Central Java and Tanah Lot Temple in Bali which are two cultural heritages developed as cultural heritage tourism destinations. Both are trying to balance between the aspects of cultural heritage preservation and tourism business by emphasizing harmony between tourism aspects, utilization of cultural heritage, consume of products and experiences, and services to tourists. The results show that both destinations provide adequate space of dialectical process that is reflected from the shifting management paradigm from competitors towards collaborators relationship. Both destination managements are directed towards symbiotic cooperation in cultural heritage tourism. Preservation and tourism purposes mutually influencing each other. In Tanah Lot Temple cultural heritage tourism managed by customary village and local goverment while in Borobudur temple managed by PT. Taman Wisata Borobudur, a state owned enterprises.